The Princeton Fugitive Slave: The Trials of James Collins Johnson - Bailey, Lucy E. (Journal of Interdisciplinary Studies in Education, 2021)
This book review provides an overview of a compelling new book, titled The Princeton Fugitive Slave: The Trials of James Collins Johnson, written by Lolita Buckner Inniss (Fordham Press, 2019). Using interdisciplinary resources and an innovative methodological approach, Inniss traces Johnson's life as a man who escaped from slavery in Maryland to New Jersey and lived in the Princeton University community for 60 years. The author foregrounds Johnson's efforts to carve a life for himself within the oppressive context of slavery and the important trajectory of scholarship on intersections between universities and slavery.